PREDICTING IDH1 MUTATION AND 1P19Q CO-DELETION STATUS FOR BRAIN TUMOR. - Mrs. Disha Wankhede, Sourav Singh, Manali Bhavsar, Rasika Mahadeshwar, Sumeet Rathod (International Journal of Advanced Science and Technology, 2020)
The recent increase of machine learning and its applications in many fields like image classification, text classification and many new applications like text and image generation, visual question answering has also led to the field being used in medical sciences for various tasks. This survey presents the ML AI algorithm used specifically for solving problems for brain cancer diagnostics and cure, and pointing up clinical part of the field.  We discuss core research areas and application of tumor type classification, tumor segmentation, survival prediction and tumor mutation type prediction.